2014
DOI: 10.3109/03014460.2014.885082
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of human lip prints: a collaborative study of ethnically distinct world populations

Abstract: The remarkable feature noted after compilation of the data included pattern C (a bifurcate/branched prototype extending the entire height of the lip) being a frequent feature of the lips of all the populations studied, save for the Nigerian population in which it was completely absent and which showed a tendency for pattern A (a vertical linear groove) and a significantly higher susceptibility for combination (COM) patterns. Chi-square test and correspondence analysis applied to the frequency of patterns appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…2 They become indispensable but vary in predominance, gender and race. [3][4][5] More studies on lip prints in relation to sex for its utility as sex determination are recommended. 6 The study was conducted to assess the distribution of types of lip print among medical students and identify the predominant type in either sex.…”
Section: Introductionmentioning
confidence: 99%
“…2 They become indispensable but vary in predominance, gender and race. [3][4][5] More studies on lip prints in relation to sex for its utility as sex determination are recommended. 6 The study was conducted to assess the distribution of types of lip print among medical students and identify the predominant type in either sex.…”
Section: Introductionmentioning
confidence: 99%
“…Cheiloscopy has attracted attention of many scientists as a new tool for human identification specifically dealing with criminal cases. Many studies (Domiaty et al 2010;Sharma et al 2014) have confirmed that the LPP is unique for each individual, even in twins and within families. The stability of LPP over time has tested, validated and recommended for secure use in civil and criminal investigations (Domiaty et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have confirmed that lip print patterns may significantly vary among distinct populations. A collaborative study of populations from India, Saudi Arabia, Spain and Nigeria showed significant inter-ethnic differences [18]. The Indian prints revealed an almost equal propensity for bifurcated and incomplete vertical patterns (corresponding to types II and I`) accounting for approximately 30%.…”
Section: Discussionmentioning
confidence: 98%
“…However, the most prevalent type for each gender was not the same in every study, suggesting population-specific characteristics of lip patterns [1,3,[20][21][22]. Although some researchers claimed high success rate in the detection of gender based on the lip print pattern type, a number of studies reported that there was no statistically significant difference between male and female lip print patterns [18,23,24]. Analysis of lip patterns for sex estimation can be a subjective process which must be performed with great caution, since a false estimation can prejudice a forensic case [25].…”
Section: Discussionmentioning
confidence: 99%